RELIGION AND SOCIAL CHANGE - Chethimattam, John B (Journal of Dharma, 1984)
"If people are asked to choose between tradition and progress, tradition would perhaps be their instinctive choice, although a second thought might induce them to take a few hesitating steps in the direction of change." This is the conclusion drawn by S.C. Dube from his study of the Indian villages. I Tradition stands for religion. The fundamental drive in the thought and activities of the village group "seems to be towards the goal of adjustment of the individual to the universe." Several aspects of man's life are predestined and he has to reconcile himself to these. Still, what is predestined he can modify through his actions, and particularly determine the course of his life after death. But most of the changes in social structures and institutions are actually brought about through non-religious mundane factors that create social interaction in which presures are felt, advatnages perceived and responsibilities recognized.s Among these pressures are state compulsion, legal prescription, material culture and technology, utility, convenience, availability and price of goods. 3 Religion seems to stand often as a stumbling-block, preventing real healthy social change.